Home Schooling in the United States - Kurt J. Bauman (Arizona State University, 2002)
Home schooling is a subject of great fascination, but little solid knowledge. Despite its importance, it has received less research attention than some other recent changes in the educational system, such as the growth of charter schools. It could be argued that home schooling may have a much larger impact on educational system, both in the short and long run. This report uses the 1994 October CPS, and the National Household Education Survey of 1996 and 1999 to examine popular characterizations of the home school population. The article assembles evidence from several sources to confirm that home schooling is growing. It finds home-schooled children more likely to be middle income, white, from larger families, and from two-parent families with one parent not working. While some authors have described a division between religiously-motivated and academically-motivated home schoolers, this research finds more support for a divide based on attitude towards regular schools.